Smoking and occupational allergy in workers in a platinum refinery. Issue 6705 (14th October 1989) - Venables, K. M.; Dally, M. B.; Nunn, A. J.; Stevens, J. F.; Stephens, R.; Farrer, N.; Hunter, J. V.; Stewart, M.; Hughes, E. G.; Newman Taylor, A. J.
Abstract : OBJECTIVE–To test the hypothesis that smoking increases the risk of sensitisation by occupational allergens. DESIGN–Historical prospective cohort study. SETTING–Platinum refinery. SUBJECTS–91 Workers (86 men) who started work between 1 January 1973 and 31 December 1974 and whose smoking habit and atopic state (on skin prick testing with common allergens) had been noted at joining. MAIN OUTCOME MEASURES–Results of skin prick tests with platinum salts carried out routinely every three to six months and records of any respiratory symptoms noted by the refinery's occupational health service. Follow up was until 1980 or until leaving refinery work, whichever was earlier. RESULTS–57 Workers smoked and 29 were atopic; 22 developed a positive result on skin testing with platinum salts and 49 developed symptoms, including all 22 whose skin test result was positive. Smoking was the only significant predictor of a positive result on skin testing with platinum salts and its effect was greater than that of atopy; the estimated relative risks (95% confidence interval) when both were included in the regression model were: smokers versus non-smokers 5.05 (1.68 to 15.2) and atopic versus non-atopic 2.29 (0.88 to 5.99). Number of cigarettes smoked per day was the only significant predictor of respiratory symptoms. CONCLUSION–Smokers are at increased risk of sensitisation by platinum salts.